Teorema Pembatasan Dimensi Dua - Hendra Gunawan (Institut Teknologi Bandung, 1996)
In this paper we prove the two-dimensional restriction theorem using the Babenko-Hausdorff-Young and the Hardy-Littlewood-Sobolev inequalities.